(untitled) (Social Science Review, 2024)
Research suggests various standardized assessment tools to collect and analyze the speech of the individual with cleft lip and/or palate (CLP). Despite the importance of developing an assessment framework for the growing CLP population, documentation on Bengali cleft speech is limited. This study aims to investigate the phonetic differences that happen in the speech sound production of 3 to 5-year-old Bengali-speaking CLP children in two different contexts: single word and sentence repetition. It also aims to evaluate the effects of these two speech assessment tools in those children’s phonological evaluation to identify the proper evaluation for CLP individuals. In total, 12 Bengali-speaking CLP children from 3 to 5 years old participated in each test. Thus, data has been collected from a sample of 24 with 79-word stimuli. Two types of speech materials were used: single-word naming and sentence repetition tasks. The samples were analyzed using narrow phonetic transcription for targeted speech items. The percentage of consonants correct (PCC), percentage of correct places (PCP), percentage of correct manners (PCM), as well as phonological simplification processes (PSP) were assessed from the samples. Results showed a range of word structures and place-manner features produced by CLP children in both tasks. Also, the PCC, PCP, PCM, and PSP results were considerably less accurate in the sentence repetition task, suggesting that the task may provide a more accurate assessment of the CLP population. Social Science Review, Vol. 40(2), December 2023 Page: 205-224